Pancasila di era digital: Menjaga etika dan moralitas dalam demokrasi siber - Akbar, Maulana (Maliki Interdisciplinary Journal, 2025)
Pancasila, as the foundational ideology of Indonesia, continues to hold significant importance in shaping national identity and social values, particularly in the rapidly evolving digital era. The digital age has transformed the way people interact and participate in democratic processes, expanding opportunities for public engagement through cyberspace. However, it also introduces new challenges related to ethics and morality, such as the spread of misinformation, hate speech, and irresponsible behavior online. In this context, the principles of Pancasila provide essential guidance to uphold ethical standards and moral values within cyber democracy. By emphasizing respect, tolerance, social justice, and unity, Pancasila serves as a critical framework for fostering responsible and harmonious digital interactions. This paper explores the role of Pancasila in strengthening digital ethics and morality, aiming to create a healthy and dignified cyber democracy. The internalization and application of Pancasila values are crucial to ensuring that democratic practices in the digital realm adhere to principles of justice, humanity, and mutual respect. Ultimately, integrating Pancasila into digital life contributes to building an ethical, sustainable, and inclusive digital society.